Diagnostic Accuracy of the Alere Afinion AS100 Point-of-Care Assay to Screen for Noncommunicable Diseases Among People Living With HIV. (1st January 2023) - Bodley, Nicola; Dorward, Jienchi; Naidoo, Jessica; Letsoalo, Marothi; Ramsaroop, Kaminee; Sayed, Fathima; Sookrajh, Yukteshwar; Drain, Paul K.; Garrett, Nigel
Abstract : Supplemental Digital Content is Available in the Text.